Critical Parameters for Efficient Sonication and Improved Chromatin Immunoprecipitation of High Molecular Weight Proteins. - Nikolay A Pchelintsev; Peter D Adams; David M Nelson (PLoS ONE)
Solubilization of cross-linked cells followed by chromatin shearing is essential for successful chromatin immunoprecipitation (ChIP). However, this task, typically accomplished by ultrasound treatment, may often become a pitfall of the process, due to inconsistent results obtained between different experiments under seemingly identical conditions. To address this issue we systematically studied ultrasound-mediated cell lysis and chromatin shearing, identified critical parameters of the process and formulated a generic strategy for rational optimization of ultrasound treatment. We also demonstrated that whereas ultrasound treatment required to shear chromatin to within a range of 100-400 bp typically degrades large proteins, a combination of brief sonication and benzonase digestion allows for the generation of similarly sized chromatin fragments while preserving the integrity of associated proteins. This approach should drastically improve ChIP efficiency for this class of proteins.